Design and Validation of an Eye-Tracker-Based Software to Improve Attention in Attention Deficit Hyperactivity Disorder (ADHD): A Validation Study - Javad Rasti; Amirhasan Torabi; Nasibeh Sarrami-Foroushani; Golnaz Amiri; Negar Malekifar (Vesnu Publications, 2020)
Introduction: Attention Deficit Hyperactivity Disorder (ADHD) is a common neurobiological disorder affecting school-age children. One of the main symptoms is short attention span, which is a key factor of poor academic performance, especially in tasks requiring long-term concentration. Children with ADHD often jump from task to task without finishing any of them. They feel trapped by any task that takes longer than the time they are able to stay focused. Improving this skill usually requires breaking tasks into smaller segments while working to increase the child's attention span. The goal of this research was to design and validation of a software package based on Eye-Tracker technology to improve attention in children with ADHD. Materials and Methods: The population of this validation study consists of psychologists, who are expert in the field of learning and cognitive deficits in children and adolescents, as well as educational technologists; among them, ten people were selected on purpose. The tools used in this research included a video game developed in Unity, and Tobii Eye Tracker 4C device, and a researcher-made questionnaire for content validation. Software validity was calculated using the Kappa coefficient. Results: After applying requested revisions, the Kappa coefficient was calculated as 93.4%. Conclusion: The software seems to have appropriate content validity, and may be advised to be used to improve attention in children with ADHD.